The Philippine Coraebini Bedel, 1921 (Coleoptera: Buprestidae: Agrilini) Part 6: new and resurrected genera and new species - Bellamy, C. L. (Zootaxa, 2005)
The genus Sibuyanella Obenberger, 1942, is resurrected from synonymy under Obenbergerula Strand, 1932 and S. boudanti, sp. nov. from Bohol Island, and S. mimica, sp. nov. from Boac and Mindoro islands, are described. A second species of Philippscelus Bellamy, 1998, P. panayensis, sp. nov. is described from Panay Island, Philippines. Lumawigia gibbicephala, gen. & sp. nov. is described from Luzon Island. Three new species of Brachycoraebus Kerremans, 1903: B. mindanaoensis, B. basilanensis and B. minutus, are described. New distribution records are given for Coraebosoma manilense Obenberger, 1923 and C. samarense Bellamy, 1990. Two justified emendations: Philippscelus Bellamy, 1998 and Amorphosomatina Majer, 2000 are given. All new taxa are illustrated and keys to the species of Sibuyanella and Philippine Brachycoraebus are given.Key words: Taxonomy, new genus, new species, justified emendation, Coleoptera, Buprestidae, Coraebini, Philippines